The death cure - Dashner, James, 1972- (Dashner, James, 1972- Maze runner series., 2011)
As the third Trial draws to a close, Thomas and some of his cohorts manage to escape from WICKED, their memories having been restored, only to face new dangers as WICKED claims to be trying to protect the human race from the deadly FLARE virus.